Study of floral biology and meiotic behaviour in kantakari (Solanum surattense) (Current Horticulture, 2024)
The experiment was conducted to study floral biology and meiotic behaviour in kantakari (Solanum surattense) at the Department of Medicinal and Aromatic crops, TNAU, Coimbatore during 2019-2020. The observations were recorded on basic morphology, floral characters, floral biology and meiotic behaviour. There was about 4- 7 branches with medium violet flowers present in clusters. Heterostyly mechanism similar to brinjal is also observed. Flowers were long style set fruits, while the short and pseudo style do not come to fruiting unless it is pollinated manually. Both self and entomophilies (honey bee) mode of pollination were observed. Hence, kantakari behaves like an often cross- pollinated crop. The peak time of anthesis (64.70%) was observed between 3 and 5 AM. Anther dehiscence happens immediately after anthesis. During cell division, triad formation takes place instead of tetrad. This basic study is useful information to start breeding programme.
Keywords: Kantakari; Anthesis; Anther dehiscence; Heterostyly; Floral biology; Meiosis